Comet assay reveals no genotoxicity risk of cationic solid lipid nanoparticles. Issue 4 (15th November 2013) - Doktorovova, Slavomira; Silva, Amélia M.; Gaivão, Isabel; Souto, Eliana B.; Teixeira, João P.; Martins‐Lopes, Paula
ABSTRACT Cationic solid lipid nanoparticles (cSLN) are colloidal carriers for genes or drugs, particularly lipophilic drugs. Several reports exist on their high efficiency, but only a few studies report the effect of cSLNs on living cells. In the present work, internalization, cell viability (alamar blue assay) and genotoxic potential (alkaline comet assay) of three cSLN formulations (A–C) were evaluated in HepG2 and Caco‐2 cells. cSLN showed an average hydrodynamic diameter (z‐ave) of 141–222 nm, zeta‐potential of 55.0–72.5 mV and polidispersity indices (PdI) of 0.336–0.421. Dispersion in physiological buffers increased z‐ave and PdI. 0.01 mg ml–1 cSLN unaffected cell viability, but 1.0 mg ml–1 significantly decreased it, being cSLN‐C (Compritol‐based) the most toxic and HepG2 the most affected. DNA damage was not significantly increased by 0.1 mg ml–1 cSLN but damage was observed at 1.0 mg ml–1 cSLN‐C. Thus, no genotoxicity is to be expected at concentrations that do not reduce cell viability. Copyright © 2013 John Wiley & Sons, Ltd.